Sorption of sulfamethazine to biochars as affected by dissolved organic matters of different origin - Jia, Mingyun; Wang, Fang; Bian, Yongrong; Stedtfeld, Robert D.; Liu, Guangxia; Yu, Jinping; Jiang, Xin (Bioresource technology, 2018)
[Display omitted] •Sorption mechanism of sulfamethazine (SMT) to different biochars was observed.•The presence of methacrylic and citric acids generally enhanced SMT adsorption.•Humic acid restrained the sorption of SMT to biochar produced at 600°C.•Bovine serum albumin showed a complicated effect on the sorption of SMT species.•Sorption of SMT was insignificantly affected by malic acid and sodium alginate. Sorption characteristic of sulfamethazine (SMT) to straw biochars pyrolyzed at 300°C (BC300) and 600°C (BC600), and the effect of ubiquitous DOM were investigated. Results showed that physisorption (partition) and weak chemical binding (π-π EDA interaction) dominated the sorption of SMT to BC300 and BC600, respectively. Graphene sheets in biochar played important roles in the sorption of SMT, leading to higher sorption capacity (Kf) on BC600 (1.77mg1−nLng−1) than BC300 (0.11mg1−nLng−1). Sorption amount of SMT to BC300 was not affected by polysaccharide and malic acid, while it was slightly promoted by citric acid, but dramatically increased 1.25 times by methacrylic acid through decreasing solution pH and providing new sorption sites. Humic acid and bovine serum albumin restrained the sorption of SMT to BC600, but enhanced SMT− adsorption to BC300. The chemical nature of DOM, biochar properties and antibiotic species co-determined the impact of DOM on antibiotics adsorption.